2013
DOI: 10.1371/journal.pone.0060392
|View full text |Cite
|
Sign up to set email alerts
|

Testing Species Delimitations in Four Italian Sympatric Leuciscine Fishes in the Tiber River: A Combined Morphological and Molecular Approach

Abstract: Leuciscine fishes represent an important component of freshwater ichthyofauna endemic to northern Mediterranean areas. This lineage shows high intra-specific morphological variability and exhibits high levels of hybridization, two characteristics that contribute to systematic uncertainties, misclassification of taxa and, potentially, the mismanagement of biodiversity. This study focused on brook chub, Squalius lucumonis, an endemic taxon of Central Italy. The taxonomic status of this species has long been ques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 60 publications
0
18
0
Order By: Relevance
“…Morphological characters of this species are readily identifiable with respect to the similar S. squalus . Moreover, genetic analyses conducted on Squalius lucumonis have always underlined its full validity, unlike trout species (Ketmaier et al., ; Durand et al., , ; Rossi et al., ; Tancioni et al, ). The unproductive disputes triggered by some ichthyologists have certainly not favoured the survival of this species, already included in the Habitat Directive of 1982, currently in strong decline and on the global list of species threatened with extinction (Bianco and Ketmaier, ).…”
Section: Resultsmentioning
confidence: 99%
“…Morphological characters of this species are readily identifiable with respect to the similar S. squalus . Moreover, genetic analyses conducted on Squalius lucumonis have always underlined its full validity, unlike trout species (Ketmaier et al., ; Durand et al., , ; Rossi et al., ; Tancioni et al, ). The unproductive disputes triggered by some ichthyologists have certainly not favoured the survival of this species, already included in the Habitat Directive of 1982, currently in strong decline and on the global list of species threatened with extinction (Bianco and Ketmaier, ).…”
Section: Resultsmentioning
confidence: 99%
“…and P. septimaniae . Hybridization due to introgression has been reported in freshwater fishes (Durand, Erhan, Doadrio, Pipoyan, & Templeton, ; Machordom, Berrebi, & Doadrio, ; Perea et al, ; Tancioni et al, ) including within Phoxinus due to naturally or artificially mediated secondary contact (Palandačić et al, , ).…”
Section: Discussionmentioning
confidence: 99%
“…With the potential to identify discrete stocks phenotypically, analysis of morphometric landmarks is a valuable tool that complements other stock identification methods such as molecular approaches. Monet et al (2006), EspinosaLemus et al (2009) and Tancioni et al (2013) demonstrated that morphometric and genetic data were complementary for stock identification. The identification of discrete 'phenotypic' stocks is essential for population modelling.…”
Section: Discussionmentioning
confidence: 99%